Oral hygiene status in relation to salivary estradiol hormone level among pre-menopausal and post-menopausal Iraqi women - Al-Obaidi, Najlaa S; Qasim, Alhan A (Journal of Baghdad College of Dentistry, 2019)
Background: The menopause is physiological changes in women that give rise to adaptive changes at both systemic and oral level. During menopause, ovarian function declines and the production of sex steroid hormones reduces significantly affecting the oral tissues and periodontal structures leading to chronic inflammation of the gingiva, increased risk of tooth loss. Aim of study: The present study was designed to estimate the oral hygiene status in relation to salivary estradiol level among pre and post-menopausal women. Materials and Methods: Ninety women aged 48-52 years old, the control group consisted of 45 pre-menopausal women and the study group consisted of 45 post-menopause were examined for gingival index, plaque index and calculus index. Unstimulated saliva was collected from all women to analyze estradiol hormone level. Results: the mean rank of the gingival index, plaque index and calculus index were higher in post-menopause than that of pre-menopause group with lower level of salivary estradiol hormone (E2).These oral hygiene indices have a negative relation with estradiol (E2) hormone level in both test groups. Conclusion: Oral hygiene status affected by salivary estradiol hormone level in women. Oral hygiene status was worse among post-menopausal women and correlated negatively with salivary Estradiol hormone level.